Innovation of Electronic Licensing Information System at the Office of Investment and One Stop Integrated Services (DPMPTSP) of Bone Regency - Syarifuddin H M; Heri Tahir; Haedar Akib; Muhammad Rusdi (Jurnal Office, 2021)
The community in demanding maximum service in the concept of implementing Public Administration, has the opportunity to improve the efficiency, effectiveness and transparency of government administration, especially in innovation-based services. This study focuses on describing the implementation of e-Government in supporting the effectiveness of permit issuance services in Bone Regency. The stages of data collection used were observation, review of related documents and also interviews involving 5 elements representing the Bone Regency DPMPTSP office. The data collected were analyzed using the interactive model proposed by Miles, Huberman and Saldana.is still sustainable because it is still undergoing a development process and has received visits from several agencies in order to see, study, internalize, adapt and adopt SIMPEL innovations; leaders always keep abreast of technological developments that are tailored to the needs of the community, such as procurement, development and repair; or SIMPEL mobile-based service system provides convenience for civil servant and the community in fulfilling their rights while providing satisfaction and improving performance and services to the community; or SIMPEL innovation provides ease of synergy with the community in managing the performance and discipline of civil servant and the community to improve performance; or SIMPEL-based service innovations can be widely accessed by the community based on the type of service needed.